TEACHERSâ ATTITUDES AND TECHNOLOGY USE IN INDONESIAN EFL CLASSROOMS - Hilda Cahyani; Bambang Yudi Cahyono (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
The use of technology in education deals with two major aspects: mode and content. Nowadays, second-language teachers have the options to use technology, either web-based or non web-based, to help learners learn the target language (content) successfully. This paper aims at reporting research findings on the types of technology that the teachers use in their classrooms, how they apply them, and why they decide to use them. It also explores the teachersâ attitudes towards the use of technology and the extent to which certain types of technology have affected language learning achievement of their students.